Enhancement of Solar PV Panel Using Single Integral Sliding Mode MPPT Control - Rahul, I.; Hariharan, Dr. R. (International Journal of Integrated Engineering, 2022)
The maximum power extraction using single integral sliding mode control scheme is established from the sliding mode control scheme. The sliding mode control (SMC) scheme extracts the maximum power during the partial shading weather conditions using the effective selection sliding surface duty cycle ratio in combination of dc/dc boost converter. This dynamic operation of sliding surface selection operation in partial shading conditions aids to enhance the solar panel efficiency compared to the other existing MPPT schemes. The effective dynamic operation of sliding surface mode control is designed using feedback loop control scheme to diminish the steady state voltage error of the solar panel, further to obtain the higher sliding duty cycle ratio. The dc-to-dc boost converter is made active using sliding duty cycle ratio as input gate signal boost converter switch. Hence, higher efficiency attains at higher sliding surface duty ration. This sliding surface duty ratio is limited in sliding mode MPPT control scheme and requires the necessary advancements to achieve the maximum duty cycle ratio. The single integral sliding mode control scheme offers the maximum duty cycle ratio compared to sliding mode control scheme. Therefore, this paper discusses the single integral sliding mode MPPT control scheme. The proposed method employs the effective dynamic sliding operation using integrated steady state voltage error signal and allows to nullify the lacuna of maximum sliding duty cycle ratio. Also, the projected SISMC scheme improves the effective dynamic sliding surface switching operations compared to sliding control scheme. This allows the system to be stable and reliable switching operations. To validate the proposed MPPT control scheme the MATLAB / Simulink model was designed and verified. Also, the SMC scheme was designed and compared with the present method.